PENGARUH MODEL ROLE PLAYING TERHADAP HASIL BELAJAR PESERTA DIDIK MATERI PERUMUSAN PANCASILA KELAS 4 SDN SIDOKEPUNG I - Pasa, Kartika; Aini, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of using the role playing learning model on the learning outcomes of grade IV students of SDN Sidokepung I in the Pancasila Formulation material. This model was chosen because it is considered capable of increasing active participation of students through role-playing models that are in accordance with the learning context. This study uses a quantitative approach with an Intact Group Comparison experimental design involving two groups: an experimental class that applies role playing and a control class with a conventional learning model. Data were collected through learning outcome tests and analyzed using the independent sample t-test. The results showed that there was a significant difference between the two groups, where the average value of the experimental class (91.29) was higher than the control class (85.88), with a significance value of p = 0.000 (p <0.05). This study proves that the role playing model is effective in improving student learning outcomes. Therefore, this model can be used as an alternative interesting and innovative learning strategy, especially in Pancasila education.